Fire as a Removal Mechanism of Pyrogenic Carbon From the Environment: Effects of Fire and Pyrogenic Carbon Characteristics - Doerr, Stefan H.; Santín, Cristina; Merino, Agustín; Belcher, Claire M.; Baxter, Greg (Frontiers in Earth Science, 2018)
Pyrogenic carbon (PyC, charcoal) is produced during vegetation fires at a rate of ~ 116–385 Tg C yr-1 globally. It represents one of the most degradation-resistant organic carbon pools, but its long-term fate and the processes leading to its degradation remain subject of debate. A frequently highlighted potential loss mechanism of PyC is the consumption of PyC in subsequent fires, however, only three studies to date have tested this hypothesis with reported losses of <8-37%. The effects of PyC chemical characteristics and fire conditions on PyC loss in wildfires remain unexplored. To address this, we placed materials with different degrees of thermal and chemical recalcitrance (A: wildfire charcoal, B: slash-pile charcoal, C: pine wood and D: cedar wood) on the forest floor surface just before a high-intensity and a low-intensity boreal wildfire. Mass losses were highly variable and dependent not only on fire-, but also sample characteristics. Losses across both fires were for A: 66.5±25.2%, B: 41.7±27.2%, C: 78.2±14.9% and D: 83.8±18.9%. Mass loss correlated significantly with maximum temperature (Tmax) recorded on sample surfaces using thermocouples (r=0.65, p=0.01), but only weakly (r=0.33) with time >300C. Mass losses also showed a significant negative correlation (r=-0.38, p=0.05) with thermal recalcitrance (T50) determined using Differential Scanning Calorimetry (DSC) and Tmax with charcoal reflectance (Ro) determined after the fires (r=0.46, p=0.05). Losses in the high-intensity fire were significantly higher (p=0.05) than in the low-intensity fire, but the latter had a higher rate of conversion of fuel to PyC. Our results demonstrate that exposure to fire can indeed be a significant removal mechanism for PyC that remains exposed on the ground fires. The losses found, however, are likely to represent an extreme upper range as most PyC produced in a fire would not remain exposed on the ground surface by the time the next fire occurs. Our data also demonstrate, for real wildfire conditions, the (i) contrasting resistance of different PyC types to combustion and (ii) contrasting net PyC losses between different fire intensities. The DSC and reflectance results support the usefulness of these analyses in reflecting thermal degradation resistance and temperature exposure under actual